Depolymerization of rigid polyurethane waste by catalytic glycolysis with diethylene glycol - Oleksandr S. Ivashchuk; Wolodymyr Ya. Suprun; Volodymyr M. Atamanyuk; Volodymyr S. Kurhanskyi; Andriy O. Nahurskyi; Roman A. Chyzhovych (South African Journal of Chemical Engineering)
Glycolysis of rigid polyurethane (PU) waste has been investigated to check the possibility of the recycling of polyol from industrial furniture production. The glycolysis reaction was performed at a constant temperature. Diethylene glycol and sodium acetate were used as the solvent and catalyst, respectively. The recovered polyols were characterized by hydroxyl value (HV), dynamic viscosity, and FTIR (Fourier-transform infrared spectroscopy) spectroscopy. The HV of glycolysis products was about 200–800 mg KOH g-1. The HV depends on the applied DEG:PU mass ratio and on the reaction's time. The glycolysis product containing recovered polyols was directly used without purification for further PU synthesis. The recovered PU materials were investigated using TGA (thermogravimetric analysis) and SEM (scanning electron microscopy) microscopy.